The Emphasis of the Development of the Scientific School of Management Theory - I. K. Musayelyan (Управление)
The article analyzes current trends in the development of the scientific school of management theory. The author has tried to highlight the most important problem areas in the field of modern management. Focusing on the problems of cultural contents, functional management and processes of development, adoption and implementation of managerial decisions, the author examines the state and comes to the conclusion that modern management is need to be systematized, and sometimes to re-examine views.